2022
DOI: 10.1007/s12144-021-02556-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mental health prevalence and its risk factors in South East Asia

Abstract: With the record surge of positive cases in Southeast Asia, there is a need to examine the adverse mental effects of COVID-19 among the under-researched countries. This study aims to synthesize the extant literature reporting the effects of COVID-19 pandemic on the psychological outcomes of people in Southeast Asia, and its risk factors. A scoping review was adopted targeting articles published in PubMed, Google Scholar and Scopus from January 2020 to March 30, 2021. Articles were screened using predetermined e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…This is a sub study of a wider review study that was undertaken utilizing a flexible and iterative methodology to address a broad variety of research [ 25 , 26 ]. A five-stage framework [ 27 , 28 ] was used and reported in congruity with the regulation in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for scoping reviews [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…This is a sub study of a wider review study that was undertaken utilizing a flexible and iterative methodology to address a broad variety of research [ 25 , 26 ]. A five-stage framework [ 27 , 28 ] was used and reported in congruity with the regulation in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for scoping reviews [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…On a national scale, it is conservatively estimated that the economic cost of mental health issues at work will be RM14.46 billion in 2018, or 1% of GDP, with costs for absenteeism (RM3.28 billion, 0.23%), presenteeism (RM9.84 billion, 0.68%), and staff turnover (RM1.34 billion, 0.09%). Even though the financial costs are high, less than 1% of Malaysia's annual health budget is set aside for mental health-related issues (Balakrishnan et al, 2023;Cheah et al, 2023;Kamaruddin et al, 2022;Munawar et al, 2022;Pinheiro et al, 2017;Samy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the research in the South East Asian context highlighted the prevalence of anxiety, depression and stress among students [10]. Finally, in the scoping review on pandemic and mental health of students reveal that female students pursuing final year courses at higher education institutions (HEI) were more vulnerable to learning issues [11]. Pham and Ho [12] reported that private universities quickly followed the global trend of e-learning and adopted innovative practices proportionally more than government institutions in Vietnam.…”
Section: Introductionmentioning
confidence: 99%